The Contribution of Female Muslim Scavenger in Supporting the Family Economy - Suhertina Suhertina (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This research aims to know the phenomenon of contribution of female muslim scavenger in improving the family economy and the supporting factor and its inhibition factor. The type of this research was descriptive qualitative. The research subjects were 8 female muslim scavengers, their husbands, and kids. Data were collected through interview, documentation, and observation. The technique of data analysis used narrative technique. The research results show that female muslim scavengers in Pekanbaru city are very helpful in alleviating the burden and responsibility of their husbands. They choose to work as a scavenger because it can assist paying the house rent, kids’ school tuition fee, electricity, and other daily life needs. They work as a scavenger with work hours start from 6 a.m until 10 a.m, continued after Zhuhur prayer until night. The average income they obtained is IDR 800.000,- per month. The supporting factors that make them become scavengers are because the goods collected are easily obtained while the inhibiting factors are the rainy weather, suspicion from the residents due to allegations of theft and age. Keywords: Female Muslim, Scavenger, Family Economy